ISSUES OF THEORETICAL-LEGAL IMPROVEMENT OF PROSECUTOR'S VERIFICATIONS OVER THE IMPLEMENTATION OF LAWS - Djumayev Shokhjakhon (Scholar Express Journals, 2025)
This article discussed the prosecutor's actions on the implementation of the laws, their specifics and the subject of these investigations and the legal attitude towards the prosecutor's investigation. It is theoretically and legally justified that compliance with international treaties ratified by the Republic of Uzbekistan should be included in the framework of the subject of prosecutor's investigations over the implementation of laws. A scientific discussion has been initiated with the opinions of a number of legal scholars, and author's definitions of certain concepts have been developed. Some foreign countries experience has been cited. The importance of prosecutorial investigations over the implementation of the laws was analyzed in harmony with the tasks set out in the “development strategy”and proposals were put forward.
Keywords: Control over the implementation of laws; prosecutor's verification; prosecutor's supervision